Contact morphology of sand particles in dunes - Fernando Alonso-Marroquin; Sarmad Zafar Khan; Abdullah Alqubalee; Peter Mora; Abdullatif Al-Shuhail (Scientific Reports)
Abstract This study presents an analysis of the morphology of sand particles and their contacts using high-resolution microcomputer tomography (CT) and scanning electron microscopy (SEM). Raw 3D images are filtered, binarized, and smoothed to distinguish the granular space from the void space. The 3D granular space is segmented via an advanced adaptive watershed algorithm. The grain segmentation is used for contact detection and contact network extraction. The topography of each grain is diverse, fascinating, and shaped by a landscape of ridges and basins. This topography is reflected in the way the grains come into contact. Unlike the common conception of point contacts, we observe contacts over large surface areas, concave-like contacts due to ridge-basin interactions, and doughnut-like contacts due to incomplete contact between high ridges and deep basins. Although most of the interactions are due to a single contact, a significant number of multiple contact interactions are observed. SEM images show two key features: First, the sand surfaces are not quartz-clean but are coated with clay particles. Second, the basins are not empty but are partially filled with silt particles that are cemented with clay. This is a comprehensive experimental investigation to determine the basis for advanced contact models of the micromechanical investigation of the strength of sand aggregates and wave propagation herein. The proposed micro- and nanocharacterization of contact morphologies paves the way for future investigations of contact interaction in granular materials on Earth and beyond.